Isolated nocturnal hypertension is associated with increased left ventricular mass index in children - Seeman, Tomáš; Hradský, Ondřej; Gilík, Jiří (Pediatric nephrology (Berlin, Germany), 2021)
BACKGROUND: Isolated nocturnal hypertension (INH) is associated with increased prevalence of left ventricular hypertrophy (LVH) and cardiovascular morbidity and mortality in adult patients. Unlike in adults, data illustrating the possible association between INH and cardiac target organ damage is lacking in children. This study aimed to investigate whether INH is associated with increased left ventricular mass index (LVMI) and LVH in children. METHODS: Retrospective data from all untreated children with confirmed ambulatory hypertension (HT) in our center was reviewed. Ambulatory blood pressure monitoring (ABPM) and echocardiography were performed concurrently. Ambulatory normotensive children served as controls. LVH was defined as LVMI ≥ 95th percentile. RESULTS: There were 102 ABPM studies; of these, 79 children had renal HT, and 23 had primary HT. Median age of children was 13.2 years (3.8-18.9). Nineteen children had INH, 9 children had isolated daytime HT, 54 had daytime and nighttime HT, and 20 were normotensive. The LVMI adjusted for age (patient's LVMI/95th percentile of the LVMI) was significantly higher in children with INH than in normotensive children (0.83 ± 0.03 vs. 0.74 ± 0.03, p = 0.03). Left ventricular hypertrophy was present in 11% of children with INH; this was not significantly higher than in normotensive children (0%, p = 0.23). CONCLUSIONS: This study investigated the association between INH and cardiac structure in children with primary and renal HT and showed children with INH had higher LVMI adjusted for age than normotensive children and children with INH had similar LVMI adjusted for age to children with isolated daytime HT.
Keywords: LVMI; hypertenze; Hypertrophy, Left Ventricular; dítě; předškolní dítě; hypertrofie levé komory srdeční; Children; Adolescent; lidé; Blood Pressure Monitoring, Ambulatory; Isolated nocturnal hypertension; Echocardiography; krevní tlak; Left ventricular hypertrophy; Ambulatory blood pressure monitoring; retrospektivní studie; Hypertension; Child, Preschool; ambulantní monitorování krevního tlaku; Child; Blood Pressure; Retrospective Studies; mladiství; Humans